Study of the patterns of periodontal destruction in smokers with chronic periodontitis - Anil Sukumaran (Wolters Kluwer Medknow Publications, 2008)
Cigarette smoking is a well-established risk factor for periodontitis and carries an increased risk for loss of periodontal attachment as well as for bone loss. Aims: The purpose of the study was to investigate the pattern of the intraoral distribution of periodontal destruction among cigarette smokers with periodontitis by assessing the periodontal probing depth (PPD) and clinical attachment level (CAL). Materials and Methods: Thirty smokers with chronic periodontitis were enrolled in the study. PPD, CAL, plaque index (PI), and bleeding on probing (BOP) were measured. The data was pooled for the anterior sextant and the posterior sextant as well as for the facial and lingual surfaces. The degree of periodontal destruction was compared in these sextants. Statistical Analysis: Comparisons were made between maxillary anterior, maxillary posterior, mandibular anterior, and mandibular posterior using the one-way analysis of variance (ANOVA) test. When the overall ANOVA showed statistical significance, post hoc testing (Tukey-Kramer multiple comparisons test) was performed to explore the differences between any two groups. P -values < 0.05 were considered significant. Results: The maxillary anterior sextant showed significantly higher PPD and CAL loss than the other sextants. Similarly, the maxillary palatal area showed higher probing depth and clinical attachment loss than the facial sites and the mandibular regions. Conclusions: From the results it can be concluded that there is variation in the periodontal tissue destruction in different areas of the oral cavity, with the maximum periodontal destruction in the maxillary palatal region. These observations emphasize the deleterious effects of smoking on the periodontal tissues.